Kemampuan Literasi Numerasi Matematika Siswa pada Materi Statistika - Suzana, Yenny; Zaiyar, M.; Nurmayadani, Nurmayadani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to explore high school students’ numeracy literacy skills in understanding statistical material through a descriptive qualitative approach. The research involved 25 tenth-grade students from SMA Negeri 2 Kejuruan Muda, selected purposively based on varying levels of numeracy proficiency. Data were collected using context-based diagnostic tests and semi-structured interviews, and analyzed through the stages of data reduction, presentation, and conclusion drawing. The findings indicate that only a small portion of students were able to accurately interpret numerical information and relate it to real-life contexts. Students with moderate proficiency tended to rely on procedural routines without deeper conceptual understanding, while those with low proficiency exhibited misconceptions in interpreting symbols and contextual meaning. These results highlight the need for more contextual and interactive teaching strategies to help students develop meaningful and relevant understanding of statistical concepts. Keyword: Conceptual Understanding, Contextual Teaching Model, Mathematics, Numeracy Literacy, Statistics.